2016
DOI: 10.4334/jkci.2016.28.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Capacity of RC Composited H-Pile

Abstract: The composited structural member in which two or more materials having different stress-strain relationships (steel & concrete) has increased greatly in recent years. This paper presents the experimental results of flexural capacity of the composited H-Pile subjected to bending moment. Eight composited beams were tested under direct loading condition using the frame tester. Based on the experimental results it is noted that flexural capacity of composited H-Pile increased about 20~30% and ductility ratio signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“… Anthessius graciliunguis Do & Kajihara, 1984 was described originally as an associate of the mussel Mytilus galloprovincialis Lamarck, 1819 from Japan ( Do and Kajihara 1984 ). Kim (1998 , 2010a ) recorded four additional bivalve host species in Korea: Mizuhopecten yessoensis (Jay, 1857), Pecten albicans (Schröter, 1802), Scaeochlamys squamata (Gmelin, 1791), and Solecurtus divaricatus (Lischke, 1869) in Korea. Ueda et al (2006) found this copepod species in plankton samples in Japan.…”
Section: Taxonomic Accountmentioning
confidence: 99%
See 1 more Smart Citation
“… Anthessius graciliunguis Do & Kajihara, 1984 was described originally as an associate of the mussel Mytilus galloprovincialis Lamarck, 1819 from Japan ( Do and Kajihara 1984 ). Kim (1998 , 2010a ) recorded four additional bivalve host species in Korea: Mizuhopecten yessoensis (Jay, 1857), Pecten albicans (Schröter, 1802), Scaeochlamys squamata (Gmelin, 1791), and Solecurtus divaricatus (Lischke, 1869) in Korea. Ueda et al (2006) found this copepod species in plankton samples in Japan.…”
Section: Taxonomic Accountmentioning
confidence: 99%
“…This species is the most frequently found artotrogid copepod in Korean waters; living on sponges, among sea weeds, and on submerged fishing nets in ports ( Kim 2010a ).…”
Section: Taxonomic Accountmentioning
confidence: 99%
“…In fact, looking over the mass balance within the boundary of land and animal breeding, the animal feeds are mostly coming from outside of the farm, then the nutrients in excreta can be over the demand of the crop growing near around the animal farm [ 4 – 6 ]. Adversely from trends of increasing manure production, the arable land of 2.11 million ha in 1990 has gradually decreased to 1.73 million ha in 2012 [ 7 ], which resulted in accumulation of surplus nutrients on arable land.…”
Section: Introductionmentioning
confidence: 99%
“…According to KREI (2013), the amounts of N and P applied on agricultural land were 380,000 and 150,000 tons, respectively, via both chemical fertilizer and livestock manure compost. Livestock manure compost contributes 31.6% and 40.0% for N and P, respectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%